Place of Principles of Law in Legal Regulation of Public Relations in Conditions of Digital Society: Theoretical and Legal Research - Rostovska, Karyna; Hryshyna, Natalia; Pakhomova, Irina; Liubchyk, Viktor; Koval, Marat (Universitas Islam Negeri Antasari Banjarmasin, 2024)
Purpose of the article is to carry out original research on the place of principles of law in legal regulation of public relations in conditions of digitalization. Being a specific (fundamental, abstract, etc.) rule of law, a principle of law must be expressed in a certain external form (constitution, law, court decision, doctrine). During writing this article, a functional research, induction, deduction and classification methods was used; it allows to thoroughly reveal dynamic aspects of principles of law, their practical purpose, place and role among other elements of law and the legal system of society in general, as well as influence social relations in the form of legal regulation and other forms of legal influence (informational one, value-oriented one, psychological one, system-forming one, etc.). It was concluded that inclusion of universally recognized principles and norms of international law in the domestic legal system significantly changes its content, in a new way raises the question of interaction, hierarchy of legal acts in accordance with their legal force and the meaning of norms contained in them. Importance of principles of law is reflected in the fact that they act as a framework, a fundamental structure of the legal system; principles of law are a guide in the process of law development and formation; they significantly influence the formation of people’s legal awareness, can be a direct basis for making individual legal decisions in specific cases; in the case of gaps in the legislation, principles of law can be used as a legal ground when considering the issue of law, while they act as a source of law, principles of law contribute to the correct interpretation of legal norms. The state of implementation of the fundamental principles of the Union in the founding states, using the example of the Federal Republic of Germany and the French Republic, as well as problems with the implementation of the principles of the law of the Republic of Poland, were studied. Thus, Germany and France today have a fairly high level of implementation and compliance with the main principles of European Union law, while Poland has recently had certain problems with this. So, over the past 7 years, this state has violated EU values in two categories at once - in the category of personal and political rights. In 2023, cases of legitimate abortions were limited in the Republic of Poland, which violated the right to the integrity of the individual and its inviolability, which is one of the main values of the European Union. In 2022, the European Commission filed a lawsuit against Poland to the European Court of Justice regarding violations of the latest requirements of the EU Treaty regarding the principle of judicial independence.